2022
DOI: 10.3389/fenvs.2022.1045414
|View full text |Cite|
|
Sign up to set email alerts
|

Green supply chain integration, supply chain agility and green innovation performance: Evidence from Chinese manufacturing enterprises

Abstract: Despite widespread attention on the significance of green supply chain integration (GSCI), there is still limited research on how GSCI can improve firms’ green innovation performance. From the perspective of the natural resource-based view and dynamic capability theory, based on the theoretical logic of “resource-capability-performance”, this study aims to explore the relationship between GSCI and firms’ green innovation performance and its intrinsic mechanism. In order to test the research model, this study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…In accordance with scholarly endeavors to comprehend the influence of innovation on supply chains [3,36], the present study contributes to the scholarly conversation surrounding green innovation and the resilience of supply chains. To enhance the comprehension of how green innovation can enhance resilience within the Turkish manufacturing sector, this study utilizes the resource-based view (RBV), dynamic capabilities theory, and contingency theory.…”
Section: Introductionsupporting
confidence: 57%
“…In accordance with scholarly endeavors to comprehend the influence of innovation on supply chains [3,36], the present study contributes to the scholarly conversation surrounding green innovation and the resilience of supply chains. To enhance the comprehension of how green innovation can enhance resilience within the Turkish manufacturing sector, this study utilizes the resource-based view (RBV), dynamic capabilities theory, and contingency theory.…”
Section: Introductionsupporting
confidence: 57%
“…Another study examined the environmental, social, and economic performance of green supply chain integration's influence on Chinese manufacturers' sustainable performance (Han and Huo, 2020) [10]. Investigators explored the relationship between green supply chain integration and firms' green innovation performance and its intrinsic mechanism of Chinese manufacturers (Zhang et al, 2022) [11]. Another study examined the impact of various lean manufacturing practices on sustainability performance and the mediating role of GSCM for Pakistani manufacturing firms (Awan et al, 2022) [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on the relationship between GSCI and enterprise performance has yielded mixed results. Some scholars believe that GSCI can optimize financial efficiency, improve operational efficiency, and enhance enterprise management capabilities and social benefits (Huo et al, 2015; Kim & Chai, 2016; Zhang et al, 2022). However, alternative studies have indicated that, under specific circumstances, GSCI may yield a detrimental effect on firm performance.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Consequently, Melander and Arvidsson (2022) propose that, when lacking in-house knowledge and tangible resources for green innovation, multiple partners could partake in the process, although their specific identities and roles remain uncertain. In this context, Zhang et al (2022) and Wang et al (2023) emphasize that despite the widespread recognition of the significance of GSCI, research on how GSCI can enhance firms' performance in terms of green innovation remains relatively limited.…”
Section: Introductionmentioning
confidence: 99%